Study on the Fergusson College For Drop Out Students: A Study on the Career Trajectories of Freshers in Fergusson College (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Under this investigation, a three-year entry of fresherto Fergusson College, Poona was considered and the careers of all the studentswho joined the college in the. first year class, in arts or science, in 1949,1950 and 1951, were followed until they passed out after taking the BA or B.Sc.degree, or left the college to join some other college, course or university orsimply dropped out. A period of eight years was considered adequate for thispurpose as students who did not succeed in getting the first degree within eightyears of their joining the first year class had a very remote chance of doingso after that period. Information was collected from the college records, themain sources being the admission forms, th^ results of the Poona Universityexaminations and the register of leaving certificates of the college. Noquestionnaire was issued and no interviews were taken.